2014
DOI: 10.1186/2052-336x-12-12
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of municipal landfill leachate through land treatment

Abstract: The treatment of municipal landfill’s leachate is considered as one of the most significant environmental issues. In this study a laboratory experiment was conducted through land treatment, achieving an efficient and economical method by using Vetiver plant. Moreover, the effects of land treatment of leachate of municipal landfills on the natural reduction of organic and inorganic contaminants in the leachate after the pre-treatment in the Aradkouh disposal center are invested. Three pilots including the under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 11 publications
(11 reference statements)
0
14
0
Order By: Relevance
“…After that, the clay was blended with a precise amount of Pb (NO 3 ) 2 (which was dissolved in water before blending to ensure the homogeneity of soil) to reach a target concentration of 1000 ppm (this concentration was chosen in order to test the worst-case scenario of the contaminated soil) by using the following equation (eq. 1): (1) whereas: m= weight of the solution required (g) C= target concentration of Pb (ppm) ms = specimen final weight (g) n= molecular number Ms= solution molecular weight (g/mol) η= percentage purity chemical (%) Mm= metal atomic weight (g/mol) Cement and Water Ordinary Portland cement type II (CEM II) was used as blender with distilled water.…”
Section: Experimetal Part Materials and Methods Soil Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…After that, the clay was blended with a precise amount of Pb (NO 3 ) 2 (which was dissolved in water before blending to ensure the homogeneity of soil) to reach a target concentration of 1000 ppm (this concentration was chosen in order to test the worst-case scenario of the contaminated soil) by using the following equation (eq. 1): (1) whereas: m= weight of the solution required (g) C= target concentration of Pb (ppm) ms = specimen final weight (g) n= molecular number Ms= solution molecular weight (g/mol) η= percentage purity chemical (%) Mm= metal atomic weight (g/mol) Cement and Water Ordinary Portland cement type II (CEM II) was used as blender with distilled water.…”
Section: Experimetal Part Materials and Methods Soil Samplesmentioning
confidence: 99%
“…The increase of wastes generation is becoming more and more obvious during the latest decades in Malaysia and in all over the world. Researchers have shown that between 40 to 80% of municipal solid waste is disposed of in developed countries whereas this rate reaches 60 to 90% in developing countries [1]. Several companies generate enormous quantities of residual substances that usually loaded by toxic heavy metals such as cadmium (Cd), copper (Cu), chromium (Cr), arsenic (As) and lead (Pb).…”
mentioning
confidence: 99%
“…are able to degrade various phenols such as pentachlorophenol, p -nitrophenol, and naphthalenesulphonic acids [82,83]. Though the metabolic degradation pathways are not fully understood, enzymes including phenoloxidase laccase (EC 1.10.3.2) and laccase-like enzymes are involved in the oxidation of aromatic substrates [81,84,85]. These exoenzymes can be potentially applied in the environmental degradation of phenolic pollutants.…”
Section: Extracellular Proteinsmentioning
confidence: 99%
“…Fresh leachate was obtained from Aradkouh's landfill located in Tehran, Iran. This landfill accommodates 8000 tons solid waste per day [48]. The features of raw leachate are shown in Table 4.…”
Section: Synthetic Leachate and Fresh Leachate Characteristicsmentioning
confidence: 99%